(untitled) (Acta Scientiarum. Technology, 2014)
The present work determined the effects of water with unbalanced calcium hardness/total alkalinity (CH/TA) ratio on Nile tilapia growth performance. Two unbalanced CH/TA ratios were tested for 8 weeks using one indoor system with 30 circular polyethylene 100 L tanks and one outdoor system with 36 circular polyethylene 250 L tanks. The factors and their specific levels tested were the total alkalinity of water (TA; 50 and 100 mg L-1 CaCO3) and the CH/TA ratio of water (CH/TA; 1/2, 1/1 and 5/1). In the indoor system, the 5/1 CH/TA ratio tanks had higher total ammonia nitrogen (TAN) than the 1/2 or 1/1 CH/TA ratio tanks. In the outdoor system, higher concentrations of TAN were found in the 1/2 CH/TA ratio tanks. The soil of the 5/1 CH/TA ratio indoor tanks had higher concentrations of organic carbon than the 1/2 or 1/1 CH/TA ratio tanks. The detrimental effects of the 5/1 CH/TA ratio on fish growth performance were stronger than those associated with the 1/2 CH/TA ratio. A significantly better food conversion ratio was observed in the 1/1 CH/TA ratio outdoor tanks regardless of the TA level of the water. Â Â